Legal Perspective on the Supporting Role of Human Resource in the Islamic Banking Industry in Indonesia - Supriyatni, Renny (International Journal of Criminology and Sociology, 2021)
The purpose of this study is to search for and find a model for developing human resources competencies based on Islamic values in Islamic banking in Indonesia. The study was a descriptive-analytical study with a normative juridical approach by using library research. The findings in this study are the human resources competency development model based on Islamic values in Islamic banking in Indonesia is to use the concept of professional qualifications and employment in the Islamic banking financial industry with the criteria and concepts of having hard & soft skills competencies, including honest, transparency, trustworthy, and personal development based on worship, faith, science, charity, and missionary endeavor.